2017
DOI: 10.1049/oap-cired.2017.0340
|View full text |Cite
|
Sign up to set email alerts
|

Charging electric vehicles, baking pizzas, and melting a fuse in Lochem

Abstract: To evaluate the impact of the energy transition on distribution grids, a year 2025 scenario stress test was conducted in a real Dutch distribution grid. For this, the authors confronted the local low-voltage grid of a village with 20 electrical vehicles and ovens. The result was a short service interruption which could not be avoided by control. Furthermore, severe unbalance and high peak load were observed, resulting in large voltage drops and severe neutral point shifts. The obtained measurements are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…This increase of EVs leads to a large increase in loads in residential distribution grids. Field tests have shown that uncontrolled charging of EVs can lead to very high peak consumption and even outages (e.g., [2]). Therefore, smart control of EV charging is required to preserve a proper operation of the grid.…”
Section: Introductionmentioning
confidence: 99%
“…This increase of EVs leads to a large increase in loads in residential distribution grids. Field tests have shown that uncontrolled charging of EVs can lead to very high peak consumption and even outages (e.g., [2]). Therefore, smart control of EV charging is required to preserve a proper operation of the grid.…”
Section: Introductionmentioning
confidence: 99%
“…These operators are regulated entities that are required to ensure a safe, secure and efficient operation of the physical networks they control and maintain [11]. In particular, we focus on DSOs, as problems within the distribution grids are foreseen in the (near) future due to the energy transition and specifically the electrification of our energy use [12][13][14].…”
Section: Abstract Interaction Layer: the Electricity Systemmentioning
confidence: 99%
“…As discussed in Section 2.2 this load is separately connected to the network from the stadium's load, thus it does not contribute to the costs incurred by the ArenA from its CTA. However, with a significant penetration of EVs, grid congestions can be expected, which smart charging strategies can help to prevent [12,14,21].…”
Section: Flexibility Models and Profile Steeringmentioning
confidence: 99%
“…Rapid synchronised measurements and fast control are needed. Failing to accomplish the latter was partially the reason why a DSM system in another field test could not prevent a black out [7].…”
Section: Unsynchronised Measurementsmentioning
confidence: 99%